Participatory budgeting - making a case for Winnipeg - Huck, Erin (2011)
Participatory budgeting (PB) is worth considering as a planning tool. It makes claims to encourage citizenship (Schugurensky, 2004), spark “transformative community development” (Lerner, 2006) and cultivate innovative forms of governance while improving the accountability of those already in place (Wampler, 2000, 2007; Wampler & Avritzer, 2004). In North America, PB is an overlooked public engagement mechanism that can introduce citizen input into place making and a timely participatory practice. This thesis seeks to understand current PB practice, and to propose a form and function of PB for Winnipeg. Empirical research of three PB examples (Toronto Community Housing, the Neighbourhood Support Coalition in Guelph, Ontario, and the 49th Ward in Chicago, Illinois) contributes to a proposed PB framework for Winnipeg that is tested with members of the community development sector in Winnipeg.